2011
DOI: 10.1172/jci59261
|View full text |Cite
|
Sign up to set email alerts
|

Fate tracing of mature hepatocytes in mouse liver homeostasis and regeneration

Abstract: Recent evidence has contradicted the prevailing view that homeostasis and regeneration of the adult liver are mediated by self duplication of lineage-restricted hepatocytes and biliary epithelial cells. These new data suggest that liver progenitor cells do not function solely as a backup system in chronic liver injury; rather, they also produce hepatocytes after acute injury and are in fact the main source of new hepatocytes during normal hepatocyte turnover. In addition, other evidence suggests that hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
371
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(406 citation statements)
references
References 62 publications
21
371
0
3
Order By: Relevance
“…S1B). These results are consistent with recent reports of Cre expression in hepatocytes and interlobular BECs of Alb-Cre mice (16).…”
Section: Significancesupporting
confidence: 94%
“…S1B). These results are consistent with recent reports of Cre expression in hepatocytes and interlobular BECs of Alb-Cre mice (16).…”
Section: Significancesupporting
confidence: 94%
“…Intriguingly, fate‐tracing studies showed recombination additionally in the venous ECs, suggesting Lyve1 expression occurring at some developmental stage in the venous ECs. Indeed, such analogies exist, for example, the albumin‐cre transgenic line recombines floxed genes in hepatocytes and cholangiocytes despite albumin expression only in adult hepatocytes 27, 28. This occurs due to the temporal expression of the albumin gene in hepatoblasts during development, which gives rise to both hepatocytes and cholangiocytes 6, 27.…”
Section: Discussionmentioning
confidence: 99%
“…We also suggested that the centrilobular ductular reaction induced by chronic CCl 4 injury might be reversible. Although the origin of ductular cells in the ductular reaction is still debated and a recent work did not find evidence for formation of ductular cells from hepatocytes, 36 Matrigel-coated surfaces (n=4). *P value < 0.05, **P value < 0.01, compared with Dex (unpaired two-tailed t-test); # P value < 0.01, compared with control (unpaired two-tailed t-test).…”
Section: Discussionmentioning
confidence: 99%